2020
DOI: 10.7759/cureus.8011
|View full text |Cite|
|
Sign up to set email alerts
|

Big Black Brain Phenomenon: Understanding Clinicoradiological Dissociation in Non-Accidental Traumatic Brain Injury in Children

Abstract: Pediatric traumatic brain injury (TBI) is a major cause of concern worldwide. Non-accidental traumatic (NAT) brain injury is common in infants. Since infants may present with varied presentations post-NAT, a healthy suspicion is required for effective diagnosis. Infants with NAT and, rarely, accidental subdural hemorrhage may exhibit a clinicoradiologically dissociative presentation, with their behavior appearing to reflect better function than what becomes apparent with maturation. Injury to the developing br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…[ 13 ] Nonetheless, a study revealed the importance of magnetic resonance imaging follow-up in infants with non-accidental trauma (NAT) for improved brain injury characterization, prognosis, and long-term management, particularly in the “big black brain” phenomenon. [ 1 ] In settings with limited resources, a CT scan is, therefore, still the initial method of imaging the BBB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 13 ] Nonetheless, a study revealed the importance of magnetic resonance imaging follow-up in infants with non-accidental trauma (NAT) for improved brain injury characterization, prognosis, and long-term management, particularly in the “big black brain” phenomenon. [ 1 ] In settings with limited resources, a CT scan is, therefore, still the initial method of imaging the BBB.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 , 15 ] It is believed that BBB represents a decompensation of hemispheric cerebral demand as a result of SDH. [ 1 ] Numerous factors may contribute to the formation of the BBB. Due to its high morbidity and mortality, the management of BBB is still contested.…”
Section: Introductionmentioning
confidence: 99%